2014
DOI: 10.1021/ja500710m
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Discrimination between Traces of Chemical Warfare Agents and Their Mimics

Abstract: 35 methods, but most of these methods are implemented for nerve 36 agents mimics, and so there is no clear proof that they will work 37 for real CWA. 10 To complement the existing methodologies, 38 we have developed a series of new highly solvatochromic 39 fluorescent indicators for phosphorylating reagents capable of 40 developing large differences in fluorescence. In this paper, we 41 report our findings upon the selective fluorescent discrim-42 ination of real nerve agents from their mimics. 43 We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(40 citation statements)
references
References 45 publications
0
40
0
Order By: Relevance
“…Multidimensional sensing devices, which offer advantages in accuracy, diversity and capability for the simultaneous detection and discrimination of multiple analytes, have received increasing attention in recent years 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 . Traditionally, three strategies are often employed to construct multidimensional sensing systems: i) combining a variety of cross-reactively colorimetric or fluorometric indicators (i.e.…”
mentioning
confidence: 99%
“…Multidimensional sensing devices, which offer advantages in accuracy, diversity and capability for the simultaneous detection and discrimination of multiple analytes, have received increasing attention in recent years 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 . Traditionally, three strategies are often employed to construct multidimensional sensing systems: i) combining a variety of cross-reactively colorimetric or fluorometric indicators (i.e.…”
mentioning
confidence: 99%
“…Between the many fluorescent indene derivatives we have prepared, we selected an array of fluorogenic probes for its ability to discriminate between nerve agents, sarin, soman, tabun, VX and their mimics, in water or organic solvent, by qualitative fluorescence patterns and quantitative multivariate analysis, thus making the system suitable for in-thefield detection of traces of chemical warfare agents, as well as to differentiate between the real nerve agents and other related compounds ( Figure 15). [50] Derivatives BD03, BD13, BD68, BD69, BD77, and BD78 underwent fluorescence quenching by photoinduced electron transfer from the free amine group. The phosphorylation of the amine group by phosphorylating agents increased the fluorescence of these compounds.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…Our work clearly showed that the response could be very different. [50] In all previously described studies, the synthesis of the reported fluorogenic probes was simple and straightforward; therefore, these fluorescent probes could be suitable for the development of upcoming practical methodologies. …”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…Nerve agents include phosphonate ester bond which is the one of highly toxic class of organophosphate and are called as chemical warfare agents . These chemical warfare agents have been used to kill the people in war or to terrify the crowd . The extreme toxicity of nerve agent involve with the inhibition of acetylcholine esterase activity .…”
Section: Introductionmentioning
confidence: 99%